Implementasi Kepemimpinan Strategis Kepala Sekolah dalam Mewujudkan Mutu Pendidikan Unggul di SMP Negeri 3 Kartasura - Farid Mahmud; Nurul Latifatul Inayati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to analyze the implementation of strategic leadership of school principals in strengthening educational quality at SMP Negeri 3 Kartasura. The research uses a qualitative approach with a sociological perspective to understand how leadership strategies are implemented in school management and learning processes. Data were obtained from key informants consisting of the principal, teachers, and students who are directly involved in educational activities. Data collection techniques included in-depth interviews, observations, and documentation. The validity of the data was ensured through source and technique triangulation, while the data analysis process followed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results of the study show that the principal’s strategic leadership contributes significantly to strengthening educational quality through several key strategies. These include the cultivation of discipline and character values, the implementation of active, creative, effective, and enjoyable learning (PAKEM), the establishment of positive routines and character habituation, active teacher involvement through professional development activities such as MGMP, the optimization of extracurricular activities and the Pancasila Student Profile Strengthening Project (P5), and supportive policies for creating a conducive learning environment. These strategies collectively enhance the quality of educational processes and outcomes, covering aspects of input, process, output, and outcome. The study concludes that strategic leadership of school principals plays a crucial role in building a positive school culture and improving sustainable educational quality.